Ukraine : Stand-By Arrangement; Review Under the Emergency Financing Mechanism. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the two-year Stand-By-Arrangement for Ukraine under the Emergency Financing Mechanism. Output growth is turning negative on the back of a large terms-of-trade shock and the ongoing credit crunch. The deterioration of the economic and financial situation is contributing to an increase in program implementation risks. Policy implementation is in line with the program. The authorities have introduced a flexible exchange rate regime, tightened monetary policy, and have taken measures to contain the 2008 government deficit.